Exploring the role of gut probiotic metabolites in the prevention and treatment of otitis media - Zheng, Bo; Jin, Haiyong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe gut microbiota derived metabolites show significant therapeutic effects on otitis media, yet the specific active metabolites and mechanisms involved remain undocumented. The primary objective of the study was to utilise a network pharmacology approach to investigate the active metabolites and underlying mechanisms by which gut microbiota exerts their effects against otitis media.MethodsA set of 110 gut microbiota-derived metabolites was retrieved from the MiMeDB database. Their target genes were identified using SEA (Similarity Ensemble Approach), resulting in 6860 human target genes. Parallelly, a differential expression analysis using the GEO dataset identified dysregulated genes in otitis media. Upon intersecting these with the metabolite target genes, we identified 268 common genes, which likely represent molecular mediators through which microbial metabolites exert its effects in otitis media. PPI interaction was used to identify the 10 hub targets. To understand the post-transcriptional regulation of these common genes, we identified miRNAs targeting them using the multiMiRR package.ResultsThe functional enrichment and disease association analyses of these genes and miRNAs revealed their significant involvement in inflammatory and immune regulatory pathways, many of which are shared with chronic otitis media pathogenesis.DiscussionOverall, this integrative approach established a strong link between gut microbial metabolites, their host gene targets, and miRNA-mediated regulatory mechanisms in otitis media. This study provided comprehensive insights warranting additional research on the therapeutic potential of metabolites for otitis media.